From training to practice: the impact of ENGAGE, Ireland's national men's health training programme. (24th December 2016) - Osborne, Aoife; Carroll, Paula; Richardson, Noel; Doheny, Martin; Brennan, Lorcan; Lambe, Barry
Abstract: Ireland's National Men's Health Policy recommended developing training programmes tailored to the needs of those working in health and allied health professionals and ENGAGE was developed to meet that recommendation. This study evaluated the impact of ENGAGE on frontline service providers' self-reported knowledge, skills, capacity and practice up to 5-months post training. Between 2012 and 2015, ENGAGE Trainers ( n =  57) delivered 62 1-day training programmes to 810 participants. This study was conducted on a subset of those training days ( n =  26) and participants. Quantitative methodologies were used to collect pre ( n =  295), post ( n =  295) and 5-month post ( n =  128) training questionnaire data. Overall, participants were highly satisfied with the training immediately post training (8.60 ± 1.60 out of 10) and at 5-month follow up (8.06 ± 1.43 out of 10). Participants' self-reported level of knowledge, skill and capacity in identifying priorities, engaging men and influencing practice beyond their own organisation increased immediately following training ( P <  0.001) and, with the exception of improving capacity to engage men and influencing practice beyond their organisation, these improvements were sustained at 5-month post training ( P <  0.001). The vast majority of service providers (93.4%) reported that ENGAGE had impacted their work practice up to 5-month post training. The findings suggest that ENGAGE has succeeded in improving service providers' capacity to engage and work with men; improving gender competency in the delivery of health and health related services may increase the utilisation of such services by men and thereby improve health outcomes for men.